THE ROLE OF PERSON-ENVIRONMENT FIT (P-E FIT) ON EMPLOYEES SUBJECTIVE WELL-BEING IN JABODETABEK - Rizkia Arfyani, Putri Aurel; Raissa Aurely; Reza Fahlevi (Ikatan Dosen Menulis, 2025)
Employees play a crucial role in the workplace due to their direct contributions to organizational productivity and development. This study aims to examine the role of Person-Environment Fit (P-E Fit) in relation to Subjective Well-Being (SWB) among employees in the JABODETABEK area. P-E Fit encompasses four dimensions: Person-Job Fit, Person-Organization Fit, Person-Group Fit, and Person-Supervisor Fit. A mismatch between individuals and their work environment can lead to stress and decreased SWB. Based on a preliminary survey of 45 participants, it was found that most of them had low levels of SWB. This research adopts a quantitative approach with a cross-sectional design and purposive sampling technique, involving 261 active employees. Data were collected through questionnaires and analyzed using SPSS with reliability tests, validity tests, and simple linear regression. The results indicate a positive and significant relationship between P-E Fit and SWB (p < 0.019) with a contribution of 2% (R = 0.24). These findings suggest that the compatibility between individuals and their work environment has a meaningful, albeit limited, impact on employee well-being. Therefore, it is important for organizations to create work environments that align with individual characteristics in order to support well-being and performance.